Dexmedetomidine alleviates propofol-induced pyroptosis of hippocampal neurons through NLRP3 inflammasome pathway. Issue 7 (3rd May 2023) - Wang, Xin; Wan, Zhenzhen
Abstract : Propofol is neurotoxic to trigger neuronal pyroptosis and dexmedetomidine possesses the ability to suppress proptosis. This study expounded on the protective functions of dexmedetomidine on propofol-induced pyroptosis of primary hippocampal neurons via NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome pathway. At first, primary hippocampal neurons underwent separation and identification and were treated with different concentrations of propofol (1, 10, and 100 μM). The toxicity of propofol in the neurons was evaluated. Prior to propofol treatment, the neurons were treated with different concentrations of dexmedetomidine (0.01, 0.1, 1, 5, and 10 μM). The viability of neurons with different treatments was detected. The mRNA expressions of homeobox A5 (HOXA5) and NLRP3 were identified. The protein levels of intracellular HOXA5, NLRP3, the N-terminal fragment of gasdermin D (GSDMD-N), and cleaved-caspase-1 and the concentrations of interleukin (IL)-1β and IL-18 were examined. Subsequently, the binding of HOXA5 to the NLRP3 promoter was detected. Joint experiments were conducted with pcDNA3.1-HOXA5 or pcDNA3.1-NLRP3 in dexmedetomidine-treated neurons. Dexmedetomidine pretreatment attenuated propofol-induced pyroptosis of hippocampal neurons, increased cell viability, and repressed NLRP3, GSDMD-N, and cleaved-caspase-1 protein levels and IL-1β and IL-18 concentrations. Dexmedetomidine pretreatment inhibited intracellular HOXA5 expression, and HOXA5 bound to the NLRP3 promoter region to promote NLRP3 expression. Overexpressing HOXA5 or NLRP3 reversed anti-pyroptosis role of dexmedetomidine pretreatment in hippocampal neurons. Dexmedetomidine pretreatment suppressed NLRP3 expression by downregulating HOXA5 expression, inhibiting propofol-induced pyroptosis in primary hippocampal neurons.